2017
DOI: 10.18632/oncotarget.16211
|View full text |Cite
|
Sign up to set email alerts
|

Low numbers of pre-leukemic fusion genes are frequently present in umbilical cord blood without affecting DNA damage response

Abstract: Despite widely accepted notion that many childhood leukemias are likely developed from hematopoietic stem/progenitor cells (HSPC) with pre-leukemic fusion genes (PFG) formed in embryonic/fetal development, the data on PFG incidence in newborns are contradictive. To provide a better understanding of a prenatal origin of leukemia, umbilical cord blood from 500 newborns was screened for the presence of the most frequent PFG associated with pediatric B-cell acute lymphoblastic leukemia. This screening revealed rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
35
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 40 publications
12
35
1
1
Order By: Relevance
“…The frequency in investigated adults was markedly lower, but that is in line with the reduced risk for ETV6-RUNX1 + leukemia in adults [48]. However, all studies confirming the presence of ETV6-RUNX1 in healthy newborns that looked at the frequency found it to be much lower [37,39]. Lausten-Thomsen et al [46] initially found1 % of ETV6-RUNX1-positive samples with a frequency of ≤ 10 −5 , therefore this study is very important in challenging the proposed frequency of the preleukemic cells.…”
Section: Etv6-runx1supporting
confidence: 53%
See 2 more Smart Citations
“…The frequency in investigated adults was markedly lower, but that is in line with the reduced risk for ETV6-RUNX1 + leukemia in adults [48]. However, all studies confirming the presence of ETV6-RUNX1 in healthy newborns that looked at the frequency found it to be much lower [37,39]. Lausten-Thomsen et al [46] initially found1 % of ETV6-RUNX1-positive samples with a frequency of ≤ 10 −5 , therefore this study is very important in challenging the proposed frequency of the preleukemic cells.…”
Section: Etv6-runx1supporting
confidence: 53%
“…The real discussion might not be whether the ETV6-RUNX1 fusion is present in healthy newborns but at what frequency. Originally, Mori et al [6] reported frequencies of 10 −4 to 10 −3 , but those frequencies were not confirmed by later studies [36,37,39,46,48]. The frequency in investigated adults was markedly lower, but that is in line with the reduced risk for ETV6-RUNX1 + leukemia in adults [48].…”
Section: Etv6-runx1mentioning
confidence: 95%
See 1 more Smart Citation
“…It has been shown to be associated with monocytic AML phenotypes and proven to be of functional relevance for leukemogenesis. [13][14][15] It is interesting to note that RKIP loss has also been observed in a variety of solid cancers and has been described as a bona fide…”
Section: Authorshipmentioning
confidence: 99%
“…Since this initial investigation, several studies have carefully analyzed the incidence of the translocation in newborns, children, and adults using fresh or frozen cord blood or peripheral blood (summarized in supplemental Table 1, available on the Blood Web site). [4][5][6][7][8][9][10][11][12][13][14] Remarkably, the suggested incidence ranged from 0.01% (equaling the corresponding leukemia rate) [7][8][9] to 8% (exceeding it by a factor of 800). 5 Because the investigated cohorts and specimens were similar, the variation was assumed to have technical explanations.…”
mentioning
confidence: 94%